2001
DOI: 10.1159/000047141
|View full text |Cite
|
Sign up to set email alerts
|

CD14 Receptor Expression and Lipopolysaccharide-Induced Cytokine Production in Preterm and Term Neonates

Abstract: CD14 expression and the capacity of mononuclear cells (MC) from preterm and term neonates to secrete the proinflammatory cytokines interleukin (IL) 1β, tumor necrosis factor α and IL-6 in response to lipopolysaccharide (LPS) was investigated and compared to that of adults. MC were incubated with various doses of LPS, and the cytokine level in the supernatants was tested. CD14 receptors on MC and the intensity of their expression were analyzed. MC of preterm and term neonates and adults responded to LPS with lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
10
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 25 publications
5
10
0
Order By: Relevance
“…TNF-a was measured by ELISA (n=5). Data representative of mean ± SD of the innate immune system to mount an effective response allowing rapid progression to multiple organ dysfunction [29].The data presented here agrees with the published literature demonstrating that neonatal monocytes produce equivalent levels of IL-6, IL-8 and IL1-b, with TNF-a the only element of the pro-inflammatory response to exhibit reduced levels following LPS and Pam-3-Cys stimulation [30][31][32][33]. The results also show that IL-10 production is significantly reduced in relation to adult monocytes following stimulation with LPS, Pam-3-Cys and TNF-a.…”
Section: Discussionsupporting
confidence: 86%
“…TNF-a was measured by ELISA (n=5). Data representative of mean ± SD of the innate immune system to mount an effective response allowing rapid progression to multiple organ dysfunction [29].The data presented here agrees with the published literature demonstrating that neonatal monocytes produce equivalent levels of IL-6, IL-8 and IL1-b, with TNF-a the only element of the pro-inflammatory response to exhibit reduced levels following LPS and Pam-3-Cys stimulation [30][31][32][33]. The results also show that IL-10 production is significantly reduced in relation to adult monocytes following stimulation with LPS, Pam-3-Cys and TNF-a.…”
Section: Discussionsupporting
confidence: 86%
“…Previous studies have shown that the basal cytokine release from blood cells is lower in children than adults, which is consistent with our data (16,17). The capacity of the infant cells to respond to E. coli culture supernatant was well developed.…”
Section: Laestadius Et Alsupporting
confidence: 93%
“…Clinical (8)(9)(10)(11)(12) and animal studies (13)(14)(15) indeed have shown reduced expression of TLR2 and TLR4, as well as diminished function in cytokine production induced by their agonists at birth, in preterm newborns. However, deficiencies in the TLR system at birth do not necessarily mean that it does not improve during the early postnatal period.…”
mentioning
confidence: 99%